Safety and efficacy of p38 mitogen-activated protein kinase inhibitors (MAPKIs) in COPD - Yu, Haichuan; Su, Xiaojie; Lei, Ting; Zhang, Lu; Feng, Zhouzhou; Zhang, Chuchu; Zhang, Meng; Wang, Yalei; Chen, Xinlong; Liu, Jian (Frontiers in Pharmacology, 2022)
Introduction: Chronic inflammation is the core mechanism of the development of COPD. Corticosteroid resistance in COPD limited its anti-inflammatory potency. p38 MAPKI was suggested as an alternative to corticosteroids, despite the fact that there is currently no systematic review evaluating existing evidence. Research Question: Based on existing evidence, what is the safety and efficacy of p38 MAPKIs in COPD patients? Article types: Systematic Review. Methods: This RCT-based systematic review with meta-analysis was conducted following the PRISMA statement. RCTs were searched and screened from 8 databases. Pooling values and associated 95% confidence intervals were deemed as statistically significant only when two-tailed P values were smaller than 0.05. Results: This study included 10 RCTs with a total population of 1751 (age, mean [SD] = 64.39 [8.06]). Safety and several efficacy indicators of lung function, inflammatory biomarkers, and quality of life were meta-analyzed. Despite the improvement of post-bronchodilator FVC, no difference between p38 MAPKI and placebo was found in both safety and efficacy. Conclusion: Compared with placebo, p38 MAPKI is safe but other than improving post-bronchodilator FVC did not show any other effects in the COPD population. Results of this study should be regarded with caution due to the small number of included studies and heterogeneity from combining different p38 MAPKIs as a whole. Systematic Review registration: PROSPERO #CRD42022302890